2017
DOI: 10.14810/ijbbr.2017.6101
|View full text |Cite
|
Sign up to set email alerts
|

Employee Engagement & Retention: A Review Of Literature

Abstract: The other objective is to analyze the critical factor which can affect the level of retention & engagement of employees with the help of literature review. For the current article the researchers reviewed 30 relevant research papers/ literature comprising employee retention& engagement concepts and practices amply. The findings of the study like good training & development, compensation structures, autonomy, quality of work life, work polices and arrangements will lead the managers and management to a new dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…Researchers and academics have identified several factors and practices that influence employee retention. The study of Munish and Agarwal (2017) propose that an effective approach to retaining employees involves implementing policies and practices that address several aspects such as work, compensation, quality of work life, and training and development. Furthermore, factors in the workplace such as effective leadership, opportunities for professional growth, maintaining a healthy work-life balance, providing training and development, offering mentorship, promoting career advancement, ensuring job satisfaction, implementing an inclusive management style, fostering a positive work environment, and providing incentives all have an indirect impact on employee retention (Aruna & Anitha, 2015).…”
Section: Concept Of Employee Retentionmentioning
confidence: 99%
“…Researchers and academics have identified several factors and practices that influence employee retention. The study of Munish and Agarwal (2017) propose that an effective approach to retaining employees involves implementing policies and practices that address several aspects such as work, compensation, quality of work life, and training and development. Furthermore, factors in the workplace such as effective leadership, opportunities for professional growth, maintaining a healthy work-life balance, providing training and development, offering mentorship, promoting career advancement, ensuring job satisfaction, implementing an inclusive management style, fostering a positive work environment, and providing incentives all have an indirect impact on employee retention (Aruna & Anitha, 2015).…”
Section: Concept Of Employee Retentionmentioning
confidence: 99%
“…This study further emphasized that in addition to career-related training and development with compensation packages, the management needs to focus on improving staff commitment for retaining them in the long run. Agrawal and Munish (2017) identified the provision for effective performance appraisal, health and safety, reward, recognition, compensation, opportunities for career development, and training as the key driving factors for staff retention. Similarly, the study emphasized that the management must offer opportunities for promotions, social recognition, and access to training and development opportunities (Milka et al, 2017).…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…This study identified career growth potential as the strongest valence and prevalence of work-life balance as the weakest one to influence the level of staff retention. Similarly, proper training and development, well-structured compensation package, job autonomy, work-life balance, work policies, and structural arrangements as the equally powerful instruments of staff retention, and their 100 percent engagement at the job were reported as the key factors for employee retention (Agrawal & Munish, 2017). Chandani et al (2016) observed that the various factors responsible for staff engagement, specifically in the case of new staff, included quality of induction programs, access to training and development, and skill certification programs.…”
Section: Introductionmentioning
confidence: 99%
“…A significant variance in TOI remains unexplored in the literature. Important topics, such as the critical role of onthe-job and off-the-job embeddedness in defining the links toward TOI (Agarwal, 2017), have also been neglected. Recently, JE has been explored to investigate TOI preventive measures such as (a) link, wherein employees have good working relationships, and each individual is officially or unofficially linked to other people, teams, and organizations; (b) fit, which refers to how compatible the employees feel with the company, organization, or the local community to which he or she belongs and how fit they feel they are for their job; and (c) sacrifice, which refers to the opportunity cost of turnover, that is, the perceived cost of physical or psychological convenience sacrificed when leaving a current job, indicating a retention or an antiwithdrawal construct (Chan et al, 2019;Hussain & Deery, 2018;Reitz, 2014).…”
Section: Introductionmentioning
confidence: 99%